The mineral weathering ability of Collimonas pratensis PMB3(1) involves a Malleobactin‐mediated iron acquisition system. (21st April 2021) - Picard, Laura; Paris, Cédric; Dhalleine, Tiphaine; Morin, Emmanuelle; Oger, Philippe; Turpault, Marie‐Pierre; Uroz, Stéphane
Summary: Mineral weathering by microorganisms is considered to occur through a succession of mechanisms based on acidification and chelation. While the role of acidification is established, the role of siderophores is difficult to disentangle from the effect of the acidification. We took advantage of the ability of strain Collimonas pratensis PMB3(1) to weather minerals but not to acidify depending on the carbon source to address the role of siderophores in mineral weathering. We identified a single non‐ribosomal peptide synthetase (NRPS) responsible for siderophore biosynthesis in the PMB3(1) genome. By combining iron‐chelating assays, targeted mutagenesis and chemical analyses (HPLC and LC‐ESI‐HRMS), we identified the siderophore produced as malleobactin X and how its production depends on the concentration of available iron. Comparison with the genome sequences of other collimonads evidenced that malleobactin production seems to be a relatively conserved functional trait, though some collimonads harboured other siderophore synthesis systems. We also revealed by comparing the wild‐type strain and its mutant impaired in the production of malleobactin that the ability to produce this siderophore is essential to allow the dissolution of hematite under non‐acidifying conditions. This study represents the first characterization of the siderophore produced by collimonads and its role in mineral weathering.